Postoperative morbidity and failure to rescue in surgery for gastric cancer: a single center retrospective cohort study of 1107 patients from 1972 to 2014 - Galata, Christian; Ronellenfitsch, Ulrich; Blank, Susanne; Reißfelder, Christoph; Hardt, Julia (Cancers, 2020)
gastric cancer; gastrectomy; complications; mortality; failure to rescue